If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 * 6 = w + 3 Multiply 9 * 6 54 = w + 3 Reorder the terms: 54 = 3 + w Solving 54 = 3 + w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 54 + -1w = 3 + w + -1w Combine like terms: w + -1w = 0 54 + -1w = 3 + 0 54 + -1w = 3 Add '-54' to each side of the equation. 54 + -54 + -1w = 3 + -54 Combine like terms: 54 + -54 = 0 0 + -1w = 3 + -54 -1w = 3 + -54 Combine like terms: 3 + -54 = -51 -1w = -51 Divide each side by '-1'. w = 51 Simplifying w = 51
| 33=4n+7n | | -2x-3(-x+2)=4 | | 6x+8=3(x+2)-4(x+3) | | -0.3p=27 | | 6x^3-13x^2+8x+1=0 | | 2y+10+10-15y= | | 47-2x=45 | | (x-3/4)=(5x-2/5) | | y=-1.5*6+7.5 | | 16+8r+-4r+4=24 | | 8c+40=3x+5 | | 2u=5u-15 | | 2(y+5)+5(2+3y)= | | x-3/4=5x-2/5 | | y=-1.5*4+7.5 | | a(23-6)-a(4+3)= | | 7.50y=300 | | x+5x-18+4x=180 | | 63-17+19=x | | 5t-4=-3t+6 | | x+2x-3+2x=180 | | 23=1+4y | | 128=(x)(x-4)(x-4) | | -78p+2p-4p+1+42= | | X-3*(X-2)=5-(X-3) | | 5.00x=850 | | 3x-35/4=-5 | | 8h+9=91 | | 9x-54=25*3x | | 7n+5=224 | | 8x+30=11x | | -2axb=a |